‘Conversion’ to Islam in Early Medieval Europe: Historical and Archaeological Perspectives on Arab and Northern Eurasian Interactions - Sara Ann Knutson; Caitlin Ellis (Religions, 2021)
In recent years, the influence of Muslims and Islam on developments in medieval Europe has captured the attention of scholars and the general public alike. Nevertheless, ‘conversion’ to Islam remains a challenging subject for historical research and demands more transdisciplinary collaborations. This article examines early medieval interactions between Muslim Arabs and Northern and Eastern Europeans as a case study for whether some individuals in Northern Eurasia ‘converted’ to Islam. More importantly, we address some key examples and lines of evidence that demonstrate why the process of ‘conversion’ to Islam is not more visible in the historical and archaeological records of Northern Eurasia. We find that, despite the well-established evidence for economic exchanges between the Islamic World and Northern Eurasia, the historical and material records are much more complex, but not entirely silent, on the issue of religious change. We also conclude that religious connectivity and exchanges, including with Islam, were common in early medieval Northern Eurasia, even if it is difficult in most cases to identify conclusive instances of ‘conversion’ to Islam.